Manipulation of halal logo: a legal study on known unreported casses in Malaysia - Abdullah, Nor Anita (Global Academic Excellence, 2018)
Halal is a key consumer issue. Thus, materials or ingredients in the product that contain non-halal will prompt a controversial issue. There were a few circumstances in which involved a famous company where most Muslims as consumer consumed the food products such as Cadbury, Starbuck, and Auntie Anne. These cases known as unreported cases as the media had highlighted the cases, released it to the attention of the public and becomes a sensitive issue as it outburst manipulation of halal. However, these cases were not brought before the court. Thus, this article attempts to discuss the manipulation of the halal logo that early granted to the manufacturers but in such cases where they had misled and manipulated the halal permission. To answer the objective, this article applied a descriptive analysis based on the unreported cases. Based on the analysis, the manufacturers claimed to be innocent as they already followed all the rules of regulation by JAKIM and successfully settled out of court.